ROLE OF SPORTS MANAGEMENT IN PREPARATION FOR FOOTBALL REFEREES IN THE CZECH REPUBLIC - Oldřich Racek; Ondřej Pelikán (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2015)
In our article we present the preparation of football referees, who are duly registered under the banner of the FACR - Football Association of the Czech Republic. We deal with referees who participate in various educational programmes and seminars led by teachers and other practitioners. The main communication represents the structure of competition in the Czech Republic, a way of organizing football referee and course preparation at individual levels of performance, which is unique within Europe. Introducing individual education programmes that the FACR used for education and training of referees. We also describe the content of curricula for football referees. An integral part of the article is also showing the claims that are arbitration subject to performance levels.